Do catálogo ao acervo vivo de um artista: uma experimentação pelo design estratégico - Rosa, Marina Ciravegna da (Universidade do Vale do Rio dos Sinos, 2022)
Catalog is a relatively generic term in the art system and, as it is published, it becomes static and temporal. However, the cataloging process allows a space for opening instead of closing the catalog. The question that motivated the study came from the need to understand, through Strategic Design, the role of catalogue, cataloging and narrative in an artist's studio. Therefore, the objective of this research is to propose, through experimentation in Strategic Design, cataloging practices that, by promoting situations of openness, foster the artist and reveal the sociocultural legacy. For that, four ways built the research method of the study, these are: the 1. way problematizing; the 2. referencing and conceptualizing way through a bibliographical and documental research positioned in theoretical and conceptual shades of the study; the 3. participating mode, which raised questions about experimentation practices in Strategic Design, associated with participant observation and document review (physical and digital) and the 4. interpreting mode, in which the results obtained, taken to a level of abstraction, were interpreted and discussed. Three plastic artists participated in the experiments proposed as opening spaces. For Lou Borghetti, two cataloging practices were proposed from the atelier's archive, speculating in relation to public participation through Instagram. At the end of the practices we managed to catalog 17 works with information sent by followers of the social network. For Ana Peña, it was proposed a practice of elaborating an annotated portfolio with the artist's saved works to observe her cataloging process speculating on the construction of a legacy. 178 works by the artist were catalogued, who was able to visualize, during the experimental practice, the chronology of her work and her legacy. Rogério Pessôa proposed a practice of cataloging his work based on the photos he took in the cloud and the posts on Instagram in a speculative effort to sensitize the artist to the possibility of promotion that cataloging allows. The artist mentally and schematically organized the types of plastic solutions he uses and created a solution while carrying out the experimental practice. Three spaces were proposed that opened up during the research: the Relational Spaces (in which the movements of the artists' ethos are synthesized), The Space of ambivalence (in which the metaprocessuality of experimentation in Strategic Design signal its openings) and the Narrative Spaces ( in which the artifacts of the experiments met with the other spaces). In these displacements between spaces, the role of the strategic designer was identified as a mediator between cataloging and the artist. The metaprocessuality of Strategic Design revealed that the collection is alive, it is in constant movement in relational spaces and is not a closure, like the static published catalog. And the experimentation in Strategic Design opened a space of ambiguity in the process, allowed a fluid posture that made sense to the artists and stimulated speculations between the studio's practices, its commitments and the artistic creation itself. The cataloging of the Acervo vivo was proposed as a possibility of promotion for the artist and a way to reveal his sociocultural legacy mediated by Strategic Design.
Keywords: Experimentação em design estratégico; Metaprocesso; Catalogação; Arte; Catálogo; Experimentation in strategic design; Metaprocess; Cataloging; Art; Catalogue; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial